Tertiary Students’ Strategies and Difficulties in Answering the TOEFL Test - Endah Anisa Rahma; Rina Syafitri; Giovanni Oktavinanda; Refanja Rahmatillah; Veni Nella Syahputri (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2022)
The recent study investigates tertiary students' perspectives on the implementation of the TOEFL benchmark score as a graduation requirement. There were 100 students chosen randomly in this study. Their perspectives were gathered through a questionnaire and an interview to know the students’ strategies and difficulties in answering the TOEFL test. The results showed that most students agree with the TOEFL benchmark as a graduation requirement however they face obstacles in answering the test. From the interview, the result showed that they had difficulties in answering the listening and grammar sections. This resulted in unfamiliarity with foreign sounds and a lack of practice. Besides, students felt that the minimum TOEFL score for the graduation requirement was beyond their ability since most students were not introduced to TOEFL from the beginning of their study. Most students used their strategies in learning TOEFL through searching some materials on the internet as well as from the module they got from English courses. Such strategies help them to increase their ability to improve their TOEFL score.